Diffusion and release of hydrogen from metals under the effect of ionizing radiation; Vacuum; Vol. 131 - Tyurin Yu. I. Yuri Ivanovich; Nikitenkov N. N. Nikolai Nikolaevich; Sigfusson T. I. Torsteynn Ingi; Khashkhash A. M. Adel Mokhammed ali; Wang Yaoming; Semkina L. I. Lyudmila Iosifovna; Dolgov A. S. Anton Sergeevich (2016, 2016)
Title screen